NIMG-44. DSC-MRI FRACTIONAL TUMOR BURDEN VOLUME PREDICTS OVERALL SURVIVAL IN UNMETHYLATED NEWLY DIAGNOSED HIGH GRADE GLIOMA. (14th November 2022) - Armstrong, Stephanie; Prah, Melissa; Connelly, Jennifer; Krucoff, Max; Mueller, Wade; Schmainda, Kathleen
Abstract: OBJECTIVE: Image maps of Fractional Tumor Burden (FTB), derived from dynamic susceptibility contrast (DSC) perfusion MRI, provide clinically meaningful information for glioma treatment management. The goal of this study was to determine if presurgical FTB is predictive of overall survival (OS) in high-grade glioma (HGG) classified according to WHO 2016 criteria. METHODS: Standardized relative cerebral blood volume (sRCBV) maps were created and co-registered with T1+C images using Horos (Version 4.0.0) and Imaging Biometrics software (Version 21.05) (Elm Grove, WI). Enhancing tumor volumes were determined from calibrated pre/post T1 difference (dT1) maps. Tissue-validated sRCBV thresholds were used to create FTB class maps within enhancing lesion with red regions (sRCBV > 1.556) indicating a high probability of vascular tumor, blue regions (sRCBV< 1.0) indicating avascular (non-tumor) tissue and yellow representing tissue with a lower probability of vascular tumor. FTB volume fractions (FTBv) for all vascular tumor (sRCBV >1.0) or the most vascular tumor (sRCBV > 1.566) were determined. Subjects were separated by MGMT methylation status. GraphPad Prism statistical software (Version 9.3.1) was used for Kaplan Meier survival analysis at 12 and 24 months with patients stratified by median FTBv. RESULTS: Forty-one subjects (23 males, 18 females) with a median age of 59.45 years were included. Median 12-month and overall survival of unmethylated groups stratified by FTBv (rCBV > 1.0) of 8.33cc was 10.69 and 15.35 months (p=.0453; p=.0317). Unmethylated subjects stratified with FTBv (rCBV > 1.566) of 7.13cc had a median survival of 10.69 and 15.20 with short- and long-term survival distinguished at 12 months (p=0.0033), 24 months (p=0.0002) and overall (p=0.0002). No significant difference in survival was found between the methylated subgroups with FTBv (rCBV > 1.0) or FTBv (rCBV > 1.566) stratified analyses. CONCLUSION: These results demonstrate that pre-surgical FTBv is predictive of OS in newly diagnosed unmethylated high-grade glioma.